Pengaruh Model Pembelajaran Time Token Terhadap Minat dan Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII SMPN 1 Srengat Blitar - Zahrotun Nahla; Yudi Krisno Wicaksono (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to determine the effect of the time token learning model on students' interests and learning outcomes in social studies class VIII SMPN 1 Srengat Blitar. This study uses a quantitative approach of the quasi-experimental design type with a nonequivalent control group design. The sample in this study consisted of 32 control class students and 32 experimental class students selected using purposive sampling techniques. The data in this study were collected through a learning interest questionnaire and learning outcome test which were then analyzed using the Independent Sample T-Test and MANOVA. From the results of this study, it can be seen that the time token learning model has an effect on students' interests and learning outcomes as evidenced by the sig. (2-tailed) value of 0.000 <0.05. The implications of this study show that the use of the time token learning model can increase student participation. The increased student participation will improve student learning outcomes to be better.